Developing stakeholder collaboration and communication for enhance project delivery - Igbokwe, Guy; Ubani, Emmanuel; Okorocha, Kevin; Anyanwu, Columbus (Journal of Commerce, Management, and Tourism Studies, 2025)
The study is aimed at developing stakeholder collaboration and communication for enhance building construction projects delivery using South East Nigeria as a study area. The problem of the study is failure of the stakeholders to collaborate and communicate among themselves impact on the overall constructability of building projects, (examples abound of failed and abandoned projects which are scattered all over the country, buildings collapse on regular basis in different parts of the country). The specific objective is to examine the influence of stakeholder collaboration and communication on enhancing constructability. The basic sources of data collected for the study are secondary data which include brainstorming, published relevant information and primary data gotten by the respondents/professionals. The researcher reviewed related literature which enabled him to develop a questionnaire. Data was collected through email, questionnaire and interview approach which was distributed among the stakeholders.  Analysis of data was carried out with Structural Equation Modelling (SEM). The results and finding shows that stakeholders are integral to the success of construction projects as they represent diverse interest groups with a shared goal of delivering the project effectively, The researcher concluded that the independent variables are significantly related to one another and have significant effect on dependent variables. Therefore, stakeholders are encouraged to adopt constructability strategy in order to improve overall project objectives.